Iran Sanctions by European Countries the Comparative Analysis of the Performance of the European Union and the US with Islamic Republic of Iran’s Nuclear Energy after the JCPOA (Joint Comprehensive Plan of Action): Array - Ghobadi Gholoujeh, Yousef; Ghasemi, Hakem; Rahim Eivazi, Abdol (Acta Universitatis Danubius. Relationes Internationales, 2021)
Iran as a developing country is in a certain stage of its social and political history. In addition to unique geographic position of this country, access to the Persian Gulf, domination on the Hormuz important and strategic strait, and coastal water suggesting stable and immutable factors in foreign policy of the Islamic Republic of Iran, this country is always looking for playing a key and influential role in the Middle East and in this regard, has better situation than the other countries. Emphasizing on the tangible and intangible national power sources and natural and traditional variables in one hand, and emphasizing on achieving the nuclear energy and software science and their applications in the fields of science and industry on the other hand, are important and challenging subjects worsening the crisis between Iran and U.S. So, the aim of this study is to evaluate the comparative approach of E.U and U.S toward Iran on the nuclear energy after JCPOA (Joint Comprehensive Plan of Action). Based on the studies, it was conclude that the EU and the US have some demands about Iran’s nuclear energy, after the JCPOA.